Stillbirth in a University Maternity of Porto-Novo, in Southern Benin: Epidemiological and Etiological Aspects.... - TONATO EPSE BAGNAN, JOSIANE ANGÉLINA ADJOUA; TOGNIFODE, Véronique; OGOUDJOBI, OGOURINDÉ MATHIEU; LOKOSSOU, Mègnissè Sèna H. S.; PERRIN, RENÉ-XAVIER (My University, 2017)
Summary: Stillbirth remains largely unknown in our developing countries, where many fetal deaths are not systematically recorded. Efforts still need to be made to understand the causes of stillbirth in Benin. Objective: To study the epidemiological and etiological aspects of stillbirth. Framework and study method: This is a retrospective descriptive study on 1,010 stillbirths collected at the University Maternity of Porto Novo in Benin from January 1, 2013 to June 30, 2016. Results: During the study period, we recorded 1,010 stillbirths out of 13,069 births. The overall stillbirth rate is 83.8%. The highest proportions of stillbirths were among women with the following characteristics: Age between 20 and 34 (80.2%), retailers/traders (55.8%), married women (87, 1%), referred from peripheral health facilities (82%), paucigest (33.5%), pauciparous (33.8%), multiparous (31.7%) and the large multiparity group (14.2%). Etiologies are haemorrhages (38.8%), infections (17.6%), vascular renal syndromes (16.4%), unknown causes (11.8%), obstructed labor (dystocia) (9.8%), Cord diseases (5.9%), fetal abnormalities (1.6%), non-infectious maternal pathologies (0.9%) and other causes (2.1%). Conclusion: Reducing stillbirth involves improving the health system and strengthening health infrastructures. Supervision of women with high-risk pregnancies, screening and management of diseases during pregnancy are necessary in order to reduce the frequency of fetal death in utero in our environment.
Keywords: Stillbirth; Frequency; Epidemiological characteristics; Etiologies